2018
DOI: 10.24171/j.phrp.2018.9.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Joint Association of Screen Time and Physical Activity with Obesity: Findings from the Korea Media Panel Study

Abstract: ObjectivesThere is evidence to suggest that sedentary behavior is associated with a higher risk of metabolic disease. The aim of this study was to investigate cross-sectional joint associations of physical activity (PA) and screen time (ST), with the risk of obesity in Korean adults.MethodsThe Korea Media Panel Study consisted of a household interview and a self-administered diary survey on media usage over 3 days. ST (hours/day) was defined as the reported daily average hours spent watching television, comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Eight articles reporting more than one health outcome were treated as independent studies . Among these studies, 21 studies (six cohort and 15 cross‐sectional studies) examined the association between total sedentary behaviour and overweight/obesity, 23 studies (13 cohort and 10 cross‐sectional studies) examined the association between total sedentary behaviour and type 2 diabetes, and 14 studies (one cohort and 13 cross‐sectional studies) examined the association between total sedentary behaviour and hypertension . Ten studies were conducted in North America, two in South America, nine in Australia, 18 in Europe, seven in Asia, and two in other regions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight articles reporting more than one health outcome were treated as independent studies . Among these studies, 21 studies (six cohort and 15 cross‐sectional studies) examined the association between total sedentary behaviour and overweight/obesity, 23 studies (13 cohort and 10 cross‐sectional studies) examined the association between total sedentary behaviour and type 2 diabetes, and 14 studies (one cohort and 13 cross‐sectional studies) examined the association between total sedentary behaviour and hypertension . Ten studies were conducted in North America, two in South America, nine in Australia, 18 in Europe, seven in Asia, and two in other regions .…”
Section: Resultsmentioning
confidence: 99%
“…-31,33-35,69-74 Ten studies were conducted in North America,27,32,34,39,49,53,58,62,65,73 two in South America,67,68 nine in Australia,30,31,[42][43][44][45]50,64,70 18 in Europe,29,33,36,37,40,41,46,47,51,[54][55][56]60,63,66,69,71,72 seven in Asia,28,35,38,48,52,57,74 and two in other regions 59,61. Total sedentary behaviour was objectively assessed in five studies using accelerometers,61,65,66,…”
mentioning
confidence: 99%
“…It has been shown that higher levels of video game addiction were associated with increased abdominal obesity [ 9 ], due to disturbed sleeping patterns. Increased screen time in adults has also been associated with higher BMI, a finding shown to be independent of PA behaviour [ 13 ]. Overall, there appears to be a positive correlation between sedentary lifestyles and obesity [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased screen time in adults has also been associated with higher BMI, a finding shown to be independent of PA behaviour [ 13 ]. Overall, there appears to be a positive correlation between sedentary lifestyles and obesity [ 13 , 14 , 15 ]. Limited research has investigated the relationship between esports participation and BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, health education efforts to combat obesity have focused on physical activity and energy balance intervention [12,13,14]. Screen time (combined use of technology devices with screens) is a measure of sedentary behavior that is also related to obesity in adults [15,16,17]. Given this background, few studies have inspected the relationship between specific forms of screen time and obesity measured using multiple assessments.…”
Section: Introductionmentioning
confidence: 99%